The effect of GeoGebra-assisted interactive learning on student mathematical achievement of coordinate system - Putri, Nur Aini; Putra, Zetra Hainul; Hermita, Neni; Tjoe, Hartono (Journal Of Teaching And Learning In Elementary Education, 2023)
This present study aims to examine the effect of GeoGebra-assisted interactive learning on student mathematical achievement of coordinate system. The study applied a quasi-experimental method that included 41 fifth grade students from a private Islamic school in Pekanbaru, Riau. The students were randomized into an experimental group (n=21) that received GeoGebra-assisted interactive learning and a control group (n=20) that received traditional teaching approach. Student mathematical achievement was measured using items of coordinate system developed by the researchers, and the data gathering in this study was analyzed using nonparametric statistical analysis. The findings indicated that there was significant statistical difference in student mathematical achievement of coordinate system between the experimental and control group (Asymp. Sig. (2-tailed) = 0.000 < 0.05)). The study concluded that the instruction based on GeoGebra-assisted interactive learning had a statistically significant positive effect on improving student mathematical achievement of coordinate system.